E-LEARNING ASSESSMENT OF LEARNING OUTCOMES OF LEARNERS - Radkevych, Oleksandr (Professional Pedagogics, 2022)
Relevance: The incessant growth of high technologies in society and education, in particular, has shifted traditional learning formats. The pandemic and military actions have compelled educators to transition the learning process to a remote format. This transition necessitates new approaches to testing and evaluating learning outcomes using electronic technologies, which are widely used in remote and blended learning. Scientific interest is sparked by mobile learning, which introduces a new phase in the educational process, taking into account various contexts through social and content interaction using personal electronic devices. Consequently, there is an urgent need to review the existing paradigm of learning and evaluation.Objective: To substantiate approaches to the implementation of electronic assessment of learning outcomes for education seekers, taking into account foreign experience.Methods: Theoretical analysis of scientific and educational-methodological literature on the research problem; comparison, systematization, and generalization of data for the generalization of theoretical materials and the specification of basic research concepts; empirical observations, modeling of educational situations.Results: During electronic learning, a continuous process of assessment of its outcomes is characteristic, in which information and communication technologies are used for the rapid transmission of respondents' answers. In this process, diagnostic (assesses the presence of subject knowledge; shows results; does not provide feedback; is not value-based; not individualized), formative (assesses the learning process; always positive; individualized; value-based; provides feedback), and summative (assesses learning outcomes; makes evaluative judgments; applied according to standards; shows shortcomings) assessment functions are implemented, depending on the stages of learning at which the assessment is conducted.Conclusions: The main obstacles to the development of electronic assessment on a school-wide scale for any subject are time and faculty preparation. There are also issues related to software for electronic assessment, such as compatibility with existing systems, scalability, performance, security, and limitations arising during updates, maintenance, and servicing. Electronic assessment is highly dependent on technological systems and tools.
Keywords: assessment of learning outcomes; electronic assessment; testing; objectivity; distance education; general secondary education